(untitled) (Eureka Journal of Humanities and Social Research, 2026)
This study analyzes the historical evolution of the Kashgar Rubab within the musical heritage of Uzbekistan and Karakalpakstan, alongside its pedagogical significance in the contemporary higher education system. Drawing on the practical experience of the Nukus branch of the Uzbekistan State Institute of Arts and Culture, the article justifies the effectiveness of integrating traditional “Master-Apprentice” methodologies with modern interactive techniques (KWL strategy) and digital visualization. The results demonstrate the role of innovative approaches in enhancing students’ technical proficiency, artistic interpretation, and cultural identification.